Coronavirus Crisis: Government Aid That Also Promotes Employee Ownership - David P. Ellerman; Tej Gonza (Intereconomics, 2020)
The premise of this paper is that state aid to distressed companies should benefit not only the current owners but also the employees, who are the ones taking personal risks to continue or restart companies. Government aid during the Great Recession was aimed primarily at restoring the status quo. In the current deeper crisis, aid should be designed to create a fairer, more inclusive and more socially responsible economy by promoting employee ownership as both an incentive and a reward. We show how the Employee Stock Ownership Plan, which has been pioneered in the US for 40 years and can be adapted to the European legal context, can be used as the vehicle for structuring this aid.
Keywords: 330